2018
DOI: 10.1093/europace/euy035
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of cardiac dyssynchrony and resynchronization therapy

Abstract: Synchronous ventricular electrical activation is a prerequisite for adequate left ventricular (LV) systolic function. Conduction abnormalities such as left bundle branch block, and ventricular pacing lead to a dyssynchronous electrical activation sequence, which may have deleterious consequences. The present review attempts to connect the various processes involved in the development of 'dyssynchronopathy', and its correction by cardiac resynchronization therapy (CRT). Abnormal electrical impulse conduction le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 141 publications
0
43
0
2
Order By: Relevance
“…Recent studies evaluated the systolic rebound stretch (SRS) for CRT response. 20,21 They found that CRT improves systolic function by converting SRS into shortening. CRT reduces SRS and increases systolic shortening of the septum and increased left ventricular systolic function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies evaluated the systolic rebound stretch (SRS) for CRT response. 20,21 They found that CRT improves systolic function by converting SRS into shortening. CRT reduces SRS and increases systolic shortening of the septum and increased left ventricular systolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Septal SRS was predictor for CRT response. 20,21 Increased SPS was related with dyssynchrony, and decreased SPS was related with extensive scar. Patients with large left ventricular scar tissue and low SPS values do not respond to CRT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our group showed that chronic total AV-block leads to structural changes (hypertrophy) and electrical remodeling (QT-time prolongation), but normal contractility (Peschar et al, 2003). On the other hand, patients treated with CRT have different levels of myocardial remodeling and heart failure, which may affect the response to pacing (Strik et al, 2013a, Nguyên et al, 2018). Results of this study might differ from patient data since long-term structural remodeling was not included in both the animal and computational experiments.…”
Section: Discussionmentioning
confidence: 99%
“…LBBB is associated with poor electromechanical function of the left ventricle, as regional delays in depolarization cause dyssynchronous activation of the ventricular walls. Reduced systolic shortening in regions of the myocardium that depolarize early during systole has been observed as the cause of poorer LV function in the setting of LBBB [7]. Cardiac resynchronization therapy (CRT) is performed by pacing both ventricles and is very effective at ceasing and even undoing the deleterious effects of LBBB on cardiac function and remodeling [8].…”
Section: Introductionmentioning
confidence: 99%